2017
DOI: 10.1007/s10482-017-0975-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota associated with tubes of Escarpia sp. from cold seeps in the southwestern Atlantic Ocean constitutes a community distinct from that of surrounding marine sediment and water

Abstract: As the depth increases and the light fades in oceanic cold seeps, a variety of chemosynthetic-based benthic communities arise. Previous assessments reported polychaete annelids belonging to the family Siboglinidae as part of the fauna at cold seeps, with the 'Vestimentifera' clade containing specialists that depend on microbial chemosynthetic endosymbionts for nutrition. Little information exists concerning the microbiota of the external portion of the vestimentiferan trunk wall. We employed 16S rDNA-based met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 71 publications
6
25
0
Order By: Relevance
“…The feather edge of the MHSZ is estimated within a range of depths, between 510-760 mbsl on the Rio Grande Cone and 500-670 mbsl on the Amazon deep-sea fan. Comparison of these depth ranges with recently published observations based on water column, seafloor and sub-bottom acoustic imagery and samples from piston cores [46,47,52] indicates that gas seeps occur both within and near the edge of the GHSZ in the two areas (Figure 1). (WOD18 [50]).…”
Section: The Edge Of the Stability Zone And Seafloor Gas Ventssupporting
confidence: 65%
See 1 more Smart Citation
“…The feather edge of the MHSZ is estimated within a range of depths, between 510-760 mbsl on the Rio Grande Cone and 500-670 mbsl on the Amazon deep-sea fan. Comparison of these depth ranges with recently published observations based on water column, seafloor and sub-bottom acoustic imagery and samples from piston cores [46,47,52] indicates that gas seeps occur both within and near the edge of the GHSZ in the two areas (Figure 1). (WOD18 [50]).…”
Section: The Edge Of the Stability Zone And Seafloor Gas Ventssupporting
confidence: 65%
“…Direct evidence of natural gas hydrate and gas seeps on the seafloor were found in the Rio Grande Cone [47] and in the Amazon deep-sea fan [48], in both areas in association with gas venting from the GHSZ. Living chemosynthesis-based communities in pockmarks in the Rio Grande Cone [51,52], in addition to acoustic disturbance caused by the presence of free gas at shallow depths (<10 m) below seafloor in sub-bottom profiles [53] are indicative of active methane seeps. Direct evidence of gas seepage was identified in the Amazon deep-sea fan by the presence of acoustic anomalies in the water column using multi-beam echo sounder backscatter data, which is also supported by the presence of remnants of chemosynthetic organisms at the seafloor [48].…”
Section: Gas Hydrate and Gas Venting Structures On Brazil's Continentmentioning
confidence: 99%
“…In contrast with González-Aravena et al (2016) who found the microbiota composition of the regular Antarctic sea-urchin Sterechinus neumayerii dominated by Alphaproteobacteria and Flavobacteria and relatively similar to the seawater's one, we noticed a shift in the dominant class of the gut content microbiota of A. agassizii with a marked enrichment in Plantomycetacia mostly represented by the Blastopirellula genus (20% of the Planctomycetes sequences). The Planctomycetes phylum (including the Planctomycetacia) has been observed at various abundances in several marine microbiotas, such as sponges (Taylor et al, 2013;Rodriguez-Marconi et al, 2015), tubeworms (Medina-Silva et al, 2018), jellyfish (Lee et al, 2018), macroalgae (Bengtsson and Øvreås, 2010) and regular sea urchins (Hakim et al, 2016). However, such a predominance has never been reported so far in marine invertebrates.…”
Section: Composition Specificity Of the Abatus Microbiotamentioning
confidence: 99%
“…However, such a predominance has never been reported so far in marine invertebrates. Accumulating evidences suggest that Planctomycetacia belonging to the Rhodopirellula-Pirellula-Blastopirellula clade could play a major role in the degradation of sulfated polymeric carbon through sulfatase enzyme activity (Glöckner et al, 2003;Wegner et al, 2013), notably under anaerobic conditions (Elshahed et al, 2007), and in interaction with marine macro-organisms (Hempel et al, 2008;Bengtsson and Øvreås, 2010;Medina-Silva et al, 2018). Therefore, a reasonable explanation for the enrichment of Planctomycetacia in the Abatus gut content would be its high concentration in sulfated compounds coupled with a low oxygenation rate, conditions that are known to occur in other irregular sea urchins (Plante and Jumars, 1992;Thorsen, 1998).…”
Section: Composition Specificity Of the Abatus Microbiotamentioning
confidence: 99%
“…In Brazil, the Rio Grande Cone Gas Hydrate Province in the Pelotas Basin [13] is one of the main areas with gas hydrate deposits with associated chemosynthetic communities [14,15], and consists of the first discovery of gas hydrates in the western South Atlantic. The direct recovery of gas hydrate was performed through sediment sampling by piston coring and the results showed that the gas was mainly composed of methane of biogenic origin [13].…”
Section: Introductionmentioning
confidence: 99%